Cross-cultural validation in social psychology: Enhancing locus of control and treatment efficacy through participation in community environmental co-governance for elderly chronic disease patients - Xiaoying Tie (Environment and Social Psychology, 2025)
Objective: To explore the mechanism through which community environmental co-governance participation influences the sense of control and treatment outcomes in elderly patients with chronic diseases, and to verify the moderating role of cultural factors.Methods: A mixed-methods research approach was employed, recruiting 927 elderly patients with chronic diseases from three countries: China, Japan, and the United States. Data were collected through questionnaire surveys, in-depth interviews, and community observations. Statistical analyses were conducted using structural equation modeling, multi-group analysis, and Bootstrap mediation tests.Results: Community environmental co-governance participation had a significant positive effect on sense of control (β=0.362, p<0.001). Physical environmental accessibility and social support networks played mediating roles in this relationship, with indirect effects accounting for 69.6% of the total effect. Sense of control significantly promoted treatment adherence (β=0.587), self-management behaviors (β=0.614), health indicator achievement rates (β=0.493), and subjective health perception (β=0.528). Cultural type significantly moderated the impact of community participation on sense of control, with stronger effects observed in collectivist cultural contexts (China β=0.637 vs. Japan β=0.438 vs. United States β=0.512).Conclusion: Community environmental co-governance participation enhances elderly patients’ sense of control through improved environmental factors, thereby promoting treatment outcomes. This mechanism demonstrates cultural specificity. The study provides theoretical foundations and practical guidance for optimizing community health governance models and designing culturally adaptive intervention programs.